(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
The treatment of freshwater snails with sub-lethal concentration of herbal molluscicides was effective in altering the amino acid profile of this snail species which contributed to the impairment of snails laying capacity. The herbal molluscicides were reported to contain diverse chemical profile; steroids and triterpenes, flavonoids, tannins and phenolic compounds in addition to the essential oils. The diversity of chemical constitution of different Callistemon species reflects diversity in its biological activities. The botanical molluscicides are of economic importance, especially in developing countries. Also, there is a continuous need to search for new plant species with ideal molluscicidal properities. Different plants have been reported as molluscicides. The present study was performed to study the molluscicidal activity of aqueous and ethanolic extracts of Khaya grandifoliola bark against freshwater snails. It is experimental study was carried out in Al-Keriab area in East Nile locality, Khartoum state/ Sudan, a total of 190 snail samples were randomly collected by using deep scoop from the main water canals supplying the irrigated schemes of the study area. The results showed that the aqueous extracts of Khaya grandifoliola barks possess100% molluscicidal property at concentration of 1 g/L.